Genotoxic and Cytotoxic Potential of Smoke Crack Cocaine on the Epithelium of the Human Oral Mucosa - Ferraz, Priscila; Chaiben, Cassiano Lima; Azevedo-Alanis, Luciana Reis; de Lima, Antonio Adilson Soares; de Lima, Raphaela Cássia; Fernandes, Ângela; Grégio, Ana Maria Trindade; Machado, Maria Ângela Naval (Journal of Dentistry Indonesia, 2016)
Crack cocaine is an illicit drug derived from cocaine. It can produce some damages to the lungs and oral cavity. Objective: The aim of this study was to analyze the frequency of micronuclei and some nuclear alterations in epithelial cells of crack cocaine users. Methods: Oral smears were collected from clinically normal-appearing buccal mucosa exfoliative cytology of 30 individuals (15 crack cocaine users and 15 controls). Results: Crack cocaine users consumed about 3.8 grams per day and the time consumption of the drug was of 6.4 (+3.3) years. The prevalence of micronuclei, binucleated cells, broken egg cells, budding cells, picnosis, karyolysis, and karyorrhexis was determined. The frequencies of micronuclei for case and control groups were, respectively, 2.87 + 3.46 and 0.57 + 1.6 (p=0.018). No statistical difference was observed for binucleated cells, broken egg cells, budding cells, picnosis, and karyolysis. The frequency of karyorrhexis was significantly increased on crack cocaine users than controls (54.07 + 38.58 and 24.87 + 23.97, p=0.001). Conclusion: Smoke crack might have a cytotoxic and genotoxic effects to the oral mucosa due to increased frequency of micronuclei and karyorrhexis. Thus, individuals who used crack cocaine in the long term need to be frequently examined in order to prevent neoplastic transformation.